A study of customer care and satisfaction towards hotel service quality. (1st January 2013) - Hung, Li-Mei; Chen, Chien-Chou
This study aims to understand customer care and satisfaction towards the quality of hotel service and explore whether there is a service gap between customer expectation and the actual quality of service. A total of 246 hotel customers participated in the study. The results indicated that customer care and satisfaction towards the quality of hotel service has highly significant linear positive correlation ( r = 0.407, p = 0.000). Comfortable environment and reasonable price are the major reasons for customer revisit (97.6%), and customer revisit also has significant correlation with gender, age, marital status, occupation and willingness to recommend the hotel to their friends and family. The study suggested that hotel businesses implement strategies to increase service qualities and establish a positive image of the hotel brand since good quality brings higher customer satisfaction.